2008
DOI: 10.1111/j.1745-4573.2008.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and Prediction Equations for Fatty Acids and Sensory Characteristics of Beef Longissimus Rib Steaks From Forage‐fed Cattle and Retail Usda Choice and Select Rib Steaks

Abstract: Rib steaks (n = 52) from forage‐fed cattle and United States Department of Agriculture Choice and Select rib steaks obtained from area supermarkets were utilized to determine correlations between fatty acids and sensory characteristics, to develop prediction models for sensory characteristics, and to determine correlations among fatty acids. The beef/brothy and beef fat sensory characteristics were positively correlated (P < 0.05) with 16:0, 16:1cis‐9 and 18:1, and negatively correlated (P < 0.05) with 15:0, α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…SFA became smaller in the order of intramuscular, intermuscular and subcutaneous fats, and MUFA content became larger in the same order. This tendency agreed with the results of earlier investigations which indicated that bovine tissues near the body surface would have a higher percentage of MUFA than internal tissue (Waldman et al 1968;Westerling and Hedrick 1979;Metlon et al 1982;Ozutsumi et al 1983;Sturdivant et al 1992;Baublits et al 2009). Besides, the amount of oleic acid (18:1) and MUFA in beef was associated with the favorable palatability attributes, and fat softness of beef Oleic acid was also recognized to reduce low-density lipoprotein or LDL without affecting high-density lipoprotein or HDL, and thus, oleic acid (Grundy and Denke 1990;Lagrost 1992;Fujiwara et al 2005).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…SFA became smaller in the order of intramuscular, intermuscular and subcutaneous fats, and MUFA content became larger in the same order. This tendency agreed with the results of earlier investigations which indicated that bovine tissues near the body surface would have a higher percentage of MUFA than internal tissue (Waldman et al 1968;Westerling and Hedrick 1979;Metlon et al 1982;Ozutsumi et al 1983;Sturdivant et al 1992;Baublits et al 2009). Besides, the amount of oleic acid (18:1) and MUFA in beef was associated with the favorable palatability attributes, and fat softness of beef Oleic acid was also recognized to reduce low-density lipoprotein or LDL without affecting high-density lipoprotein or HDL, and thus, oleic acid (Grundy and Denke 1990;Lagrost 1992;Fujiwara et al 2005).…”
Section: Resultssupporting
confidence: 92%
“…Besides, the amount of oleic acid (18:1) and MUFA in beef was associated with the favorable palatability attributes, and fat softness of beef Oleic acid was also recognized to reduce low-density lipoprotein or LDL without affecting high-density lipoprotein or HDL, and thus, oleic acid (Grundy and Denke 1990;Lagrost 1992;Fujiwara et al 2005). Meanwhile, stearic acid correlated negatively with beef flavor (Mandell et al 1998;Baublits et al 2009), and SFA has been considered to raise cholesterol levels and may even increase the risk of heart disease. As shown in Table 1, the subcutaneous adipose tissue of Japanese Black Wagyu could provide a slightly higher content of 18:1 (47.6%), a lower content of 18:0 (6.5%), and a higher ratio of MUFA to SFA (1.665) than those values of American and Australian cattle, which were 47.3%, 7.6%, and 1.59, respectively (Huerta-Leidenz et al 1993;Smith et al 1998;Chung et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In many cases the PUFA:SFA ratio is higher in beef from grass based systems than from concentrate based systems (Baublits et al, 2009). In the present study, the higher PUFA:SFA ratio in the GSPC bulls compared to the C bulls was mainly because of the lower SFA concentration of GSPC bulls which in turn could be related to the inclusion of grazed grass prior to the finishing period.…”
Section: Fatty Acid Compositionmentioning
confidence: 41%
“…Overall it appears that the sensory scores were mainly influenced by the total IMF content as the relationships between sensory scores and total IMF were stronger and more consistent than the relationships between sensory scores and individual fatty acids. In other studies PUFA were associated with a decrease in desirable flavour (such as beefy flavour) and an increase in undesirable flavour (such as grassy and milky-oily) characteristics of beef (Baublits et al, 2006(Baublits et al, , 2009. In the present study, the positive correlations between C20:5n-3 and abnormal flavour (r = 0.28, P < 0.05), between C18:3n-3 and PUFA/SFA ratio and abnormal flavour (although not significant), and the negative correlations between C20:5n-3 and overall liking (r = -0.34, P < 0.05) and between PUFA/SFA ratio and overall liking (r = -0.36, P < 0.01) support this observation.…”
Section: 3mentioning
confidence: 83%
See 1 more Smart Citation